Analysis of financial performance in central sumba regency - Margarethy Rohanie Mbado; Zet Ena; Yudith F. Lerrick; Rosliani Rangga (Institute of Computer Science (IOCS), 2023)
The research entitled Analysis of Financial Performance in Central Sumba Regency aims to analyze the Financial Performance of the Regional Financial Agency (BKD) of Central Sumba Regency from 2016 to 2019. This research is a quantitative descriptive research, with data collection methods using documentation methods. The data analysis techniques used are descriptive quantitative with the formula used, namely: Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Compatibility Ratio, and Growth Ratio. The results of the analysis show that the Financial Performance of the Central Sumba Regency BKD is seen from (1) the Regional Financial Independence Ratio, the relationship pattern is still classified as an instructive relationship pattern because the average magnitude of this ratio is 5.30% (2) the PAD Effectiveness Ratio, the effectiveness of Central Sumba Regency financial performance is not effective because the average effectiveness is still below 100%, which is 89.16%. (3) The Regional Financial Efficiency Ratio can be said to be quite efficient because the average regional financial efficiency of Central Sumba Regency is 84.17% (4) The Compatibility Ratio is known that the average regional operating expenditure is still very high at 69.40% compared to the average capital expenditure of 30.80% so it can be said that regional development still needs to be improved. The growth ratio of Central Sumba district is said to be quite good in terms of the average of 9.16%.